2021
DOI: 10.3390/cimb43030106
|View full text |Cite
|
Sign up to set email alerts
|

Genistein: A Potent Anti-Breast Cancer Agent

Abstract: Genistein is an isoflavonoid present in high quantities in soybeans. Possessing a wide range of bioactives, it is being studied extensively for its tumoricidal effects. Investigations into mechanisms of the anti-cancer activity have revealed many pathways including induction of cell proliferation, suppression of tyrosine kinases, regulation of Hedgehog-Gli1 signaling, modulation of epigenetic activities, seizing of cell cycle and Akt and MEK signaling pathways, among others via which the cancer cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 104 publications
1
42
0
Order By: Relevance
“…In agreement with the results of the present study, Polivkova and colleagues reported the antimutagenic and anti-genotoxic effects of genistein against the mutagens and carcinogens materials [26]. Moreover, the oral administration of chemoprotective agents as genistein reversed the frequency of the carcinogenesis process [27][28][29]. Furthermore, Hussein and colleagues concluded that genistein provides a chemoprotective role during the process of oral carcinogenesis [30], and it has been suggested as chemotherapeutic agent for oral carcinomas [32].…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with the results of the present study, Polivkova and colleagues reported the antimutagenic and anti-genotoxic effects of genistein against the mutagens and carcinogens materials [26]. Moreover, the oral administration of chemoprotective agents as genistein reversed the frequency of the carcinogenesis process [27][28][29]. Furthermore, Hussein and colleagues concluded that genistein provides a chemoprotective role during the process of oral carcinogenesis [30], and it has been suggested as chemotherapeutic agent for oral carcinomas [32].…”
Section: Discussionsupporting
confidence: 90%
“…Genistein is a redox active isoflavonoid [ 11 ]—a type of natural phenol—that is also biologically active as a phytoestrogen and is abundant in soybeans. In cancer cells, this phytochemical has anti-proliferative properties, recognized especially in cases of breast cancer [ 98 ]. It is suspected that genistein prevents angiogenesis, inhibits tyrosine kinases, modulates the hedgehog signaling pathway, and induces complex epigenetic changes.…”
Section: Results Of Functional Genomic Studies Of Natural Phenolsmentioning
confidence: 99%
“…Genistein possesses antitumor activities by the modulation of multiple signaling pathways, i.e., extracellular signal-regulated kinase 1/2 (ERK1/2), protein-tyrosine kinase (PTK), nuclear transcription factor-kB (NF-κB), mitogen-activated protein kinase (MAPK), and phosphoinositide 3 kinase/Akt (PI3K/Akt), matrix metalloproteinases (MMPs) and, Bcl-2-related X protein (Bax) ( Lee et al, 2012 ; Spagnuolo et al, 2015 ; Bhat et al, 2021 ) ( Figure 2 ). Genistein at higher concentration results in apoptosis mediated by inhibition of various proteins associated with primary tumor growth, i.e., cell cycle regulators (cyclin class) and the Akt family of proteins.…”
Section: Cellular and Molecular Mechanisms Of Polyphenols In Cancer: ...mentioning
confidence: 99%